The bats of the Congo and of Rwanda and Burundi revisited (Mammalia: Chiroptera) - Van Cakenberghe, Victor; Gembu Tungaluna, Guy-Crispin; Musaba Akawa, Prescott; Seamark, Ernest; Verheyen, Erik (European Journal of Taxonomy, 2017)
In 1966, Robert William Hayman, Xavier Misonne and Walter Verheyen published their listing of the Congolese, Rwandan and Burundian bat specimens in the collections in the museums of Tervuren, Brussels, Geneva, London and New York. In the fifty years that have passed since, some major changes have been introduced in the taxonomy of the Chiroptera: new species have been discovered, species have been split off, species have been moved to other genera, and additional material has been collected. We re-evaluated the data presented by Hayman et al., and supplemented this with specimen records found in the literature and in online catalogs. This resulted in 136 species, represented by 20 231 specimens (compared to 113 species and 8567 specimens originally). When available, we also recorded additional information such as locality, sex and age, collector, collection date and preservation type of the voucher specimen. The distribution maps of the Congolese taxa are revised to represent the current taxonomy, and are presented in perspective against the taxon’s Species Distribution Model to assess species distribution on the African continent. Additionally, an updated key to the various taxa is presented.